The mysterious howling - Wood, Maryrose. (The incorrigible children of Ashton Place ;, 2010)
Fifteen-year-old Miss Penelope Lumley, a recent graduate of the Swanburne Academy for Poor Bright Females, is hired as governess to three young children who have been raised by wolves and must teach them to behave in a civilized manner quickly, in preparation for a Christmas ball.